Economic aspects of the fixed combinations of lipid lowering medicines in group risks patients - M. V. Zhuravleva; M. Yu. Frolov; E. A. Luchinin; K. A. Kokushkin; E. D. Laryushkina; T. R. Kameneva; E. V. Kuznetsova (Izdatelstvo OKI, 2023)
Relevance.  Cardio-vascular diseases (CVD) are the one of the main reasons of mortality and disability. Hypercholesterinemia is a factor of CVD progression, and thus it should be corrected. Combination of statin + ezetemib is an eﬀective option of a medical technology for this purpose. Pharmacoeconomic analysis of rosuvastatin and ezetemib ﬁxed combination (FC) has been performed in this work in comparison with free combination (FrC) of these drugs.Materials and methods. Modelling of FC vs FrC in groups of CVD risk has been performed on 1-5 years horizon based on the local epidemiologic published data with aim of economic analysis. Eﬃcacy of FC and FrC, direct medical costs, including cost of drugs, hospitalizations etc. were taken into account also. ICER has been calculated and compared with willingness to pay.Results. FC usage instead FrC can prevent 2960-3055 deaths and 8880-9164 admissions to hospital caused CVD. FC decrease of ambulance cost as well as others direct medical expenditures in compare with FrC treatment on 9,3 bln RUR per 5 years. ICER has been calculated and has negative (dominant) result.Conclusion. FC usage is an economic dominant technology in compare with FrC for hypercholesterolemia control.